ChemInform Abstract: Hypervalent Iodine‐Catalyzed Oxidative Functionalizations Including Stereoselective Reactions. Issue 35 (September 2015) - Singh, Fateh V.; Wirth, Thomas
Abstract Review: [90 refs.